Bridging pedagogy and technology: Developing contextual digital story media to support foundational literacy - Fauziah, Muhardila; Perwitasari, Ningrum; Rigianti, Henry Aditia; Dzulkurnain, Mohammad Iskandar; Ikhsan, Wahyu Amirul (Edelweiss Applied Science and Technology, 2025)
The low interest and early reading skills of elementary school students in Indonesia necessitate the implementation of contextual and engaging learning innovations. This study aims to develop curriculum-aligned interactive digital storytelling media to support basic literacy. The methodology employed was a mixed-method exploratory approach, involving a quantitative survey of 238 students and 26 teachers, in-depth interviews, and analysis of curriculum documents (CP, TP, ATP). The results indicated that students exhibited a high interest in digital media featuring images (M=4.23), interactivity (M=3.95), and audio components (M=3.76), while their preference for print media was moderate (M=2.84). Teachers expressed a strong need for media that is engaging (M=4.31), aligned with the curriculum (M=4.27), and time-efficient (M=4.42). The most desired media features included interactive storytelling (M=4.30) and audio-text synchronization (M=4.17). Key challenges identified were limited time, infrastructure constraints, and insufficient digital training. Based on these findings, a BUCERI prototype was designed, incorporating interactive storytelling features, audio narration, and story creation tools. This media is tailored to curriculum competencies, adaptable to student levels, and encourages creative expression. In conclusion, BUCERI bridges the gap between pedagogy and technology, with significant implications for enhancing basic digital literacy in elementary schools.